The Impact of Digital Marketing Literacy on MSME Sales Performance: A Systematic Literature Review - Khairilisani, Destita; Widyastuti, Sri; Sudarmaji, Eka (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The decline in sales performance among Micro, Small, and Medium Enterprises (MSMEs) in Bengkulu Province poses a significant challenge, particularly in light of the national trend toward digital economic expansion. The objective of this research is to consolidate empirical evidence concerning the correlation between digital marketing literacy and the sales performance of MSMEs through a systematic literature review (SLR) of publications from 2020 to 2025. In accordance with the PRISMA protocol, 20 articles from the Scopus, Web of Science, and SINTA databases were subjected to thematic analysis. The results indicate that proficiency in digital marketing has a significant positive impact on MSME sales (β = 0.35–0.50), although this effect is mitigated by access to digital infrastructure, the age of the business owner, and the type of business. MSME proprietors aged over 45 and those located in rural areas exhibit heightened resistance to technology adoption, despite training initiatives. Significant deficiencies encompass a scarcity of regional studies in Sumatra, the absence of integrated models analysing infrastructure moderation, and the prevalence of quantitative designs lacking comprehensive investigation. This study makes a theoretical contribution by developing the Digital Literacy-Performance Nexus framework and has real-world implications for community-based digital training policy. Future research will encompass longitudinal studies and mixed-method approaches within regional contexts.